The Effectiveness of Knowledge Management and Export Performance among Malaysian SMEs: Mediated by Innovation - Jia-Qi, Khaw; Chelliah, Shankar (International Journal of Asian Social Science, 2020)
Small and Medium Enterprises (SMEs) works as the backbone of the economy. The commerce market is changing rapidly and organizations that are not developed well will struggle in order to survive in the competitive market. This brings a great challenge for SMEs in Malaysia as they are not developed in the full strength. This is where knowledge takes place as it carries the resources and values that could lead organization to gain competitive advantage. Malaysian government takes the initiative of knowledge management among Malaysian organization by making the transition from production-based economy to knowledge-based economy. Innovation came to mind for organization to reinvest themselves in order to standstill in the competitive market. Innovation works in producing a new and creative idea in implementing new products or enhancement on the existing products which could help to improve the organizational performance. This study focuses on how knowledge management and innovation affect the export performance of SMEs. There are three dimensions of knowledge management in this study, namely, knowledge acquisition, knowledge dissemination and knowledge application. This study anticipates that the three dimension of knowledge management are critical antecedents on the export performance which could lead to positive relationship with the export performance of SMEs. This research provides ideas that generate effective framework which help SMEs to grow in the export market in a longer term and lead them in identifying effective strategies and helps in improving their export performance.